2005
DOI: 10.1007/s00438-005-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

Barley necrotic locus nec1 encodes the cyclic nucleotide-gated ion channel 4 homologous to the Arabidopsis HLM1

Abstract: Barley homolog of the Arabidopsis necrotic (disease lesion mimic) mutant HLM1 that encodes the cyclic nucleotide-gated ion channel 4 was cloned. Barley gene was mapped genetically to the known necrotic locus nec1 and subsequent sequence analysis identified mutations in five available nec1 alleles confirming barley homolog of Arabidopsis HLM1 as the NEC1 gene. Two fast neutron (FN) induced mutants had extensive deletions in the gene, while two previously described nec1 alleles had either a STOP codon in exon 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 38 publications
(45 reference statements)
2
56
0
1
Order By: Relevance
“…It was therefore suggested that these genes are involved in programmed cell death. A similar CNGC gene from barley, the NEC1 gene, was also found to be involved in cell death [47]. In addition, ample evidence suggests a role for CNGCs in pollen development, consistent with independent evidence for the role of cNMPs in pollen development.…”
Section: Summary and Future Perspectivessupporting
confidence: 58%
See 1 more Smart Citation
“…It was therefore suggested that these genes are involved in programmed cell death. A similar CNGC gene from barley, the NEC1 gene, was also found to be involved in cell death [47]. In addition, ample evidence suggests a role for CNGCs in pollen development, consistent with independent evidence for the role of cNMPs in pollen development.…”
Section: Summary and Future Perspectivessupporting
confidence: 58%
“…These results suggest that the cpr22 phenotype is not caused by the loss of one of these genes or due to a CNGC11/cngc11, CNGC12/cngc12 genotype, but is rather a consequence of the AtCNGC11/12 chimeric gene. Importantly, a few alleles of a lesion-mimic mutant of barley (nec1) are also caused by the lack of function of a CNGC, which in sequence is most similar to that of the Arabidopsis CNGC4 gene [47]. Therefore, CNGCs are involved in plant defense against pathogens in both dicotyledon and monocotyledon plants.…”
Section: Cngcs and Plant Response To Pathogensmentioning
confidence: 99%
“…Barley mutants have been used to isolate or validate genes such as nitrate reductase (Somers et al, 1983), key genes in the anthocyanin pathway (von Wettstein, 2007), a gene responsible for the floral bract phenotype HOODED (Muller et al, 1995), the row-type gene SIX-ROWED SPIKE1 (VRS1; Komatsuda et al, 2007), the hull adhesion gene NAKED CARYOPSIS (NUD; Taketa et al, 2008), plant height genes UZU DWARF (UZU; Chono et al, 2003) and SLENDER1 (Chandler et al, 2002), several endosperm development genes (Felker et al, 1983;Morell et al, 2003;Rö der et al, 2006;Clarke et al, 2008), and two disease lesion mimic mutations NECROTIC1 (Rostoks et al, 2006) and NECROTIC.S1 (Zhang et al, 2009) among others. However, despite these individual achievements, with few exceptions (Pozzi et al, 2003;Rossini et al, 2006), the barley mutant resources have not yet been systematically explored using the tools of modern genetics.…”
mentioning
confidence: 99%
“…9,10 The barley LMM nec1 also has a mutation in the barley homolog of DND2/HLM1. 49 In these mutants the channel genes were knocked out making them loss of function mutants. On the other hand the aforementioned cpr22 mutant gives rise to a novel chimeric protein derived from homologous recombination of two tandemly repeated CNGC genes.…”
Section: The Ca 2+ Connectionmentioning
confidence: 99%